Penerapan Group Investigation Pada Matakuliah Ekonomi Mikro Islam Dalam Meningkatkan Aktivitas Dan Hasil Belajar Mahasiswa - Indrarini, Rachma (AL-WIJDÃN Journal of Islamic Education Studies, 2017)
Microeconomics theory of Islam is one of the basic college courses for Islamic economics programs in every university. Because of microeconomic theory of Islam is a basic course, it needs more understanding. Most of the methods used lecturing where the lecturer explains only existing theory, while the students are not allowed to discuss and develop their ideas to solve their problems. In ideal conditions, students should be active in seeking information, can solve problems related to topics using knowledge gained, and be able to work together. So this research will discuss the application of the group investigation on the subject of the microeconomic theory of Islam. The method used is PTK (Penelitian Tindakan Kelas) with two cycles. The results of this research are used group investigation on the subject of microeconomics theory of Islam can increase the activity and learning outcomes. Keywords: Group investigation, PTK, Microeconomics theory of Islam